Siliconharze, Siliconöle, Siliconfette - Walter Krauss (CHIMIA)
The higher price of the silicone products as compared with purely organic high polymers justifies their application only in those cases where they are the only possible material by virtue of one or more special properties. Their application is simplified where it is possible to process by conventional procedures. The following paper, therefore, describes by means of the example of the silicone resins, particularly the silicone coatings, the processing to insoluble end-products and discusses the most important properties along with industrial applications which can be derived from these. The use of suitable silicone resin types and selected hardener systems – especially mixtures of lead salts and soluble zinc or titanium compounds – makes it possible to carry out the normally quite slowly progressing condensation reactions of the polysiloxanes, which lead to the required degree of cure under favourable conditions. The various cross-linking reactions are explained. Heat resistance and water repellency, furthermore weather resistance and anti-adhesion effect are discussed as most important properties. The heat resistance as a characteristic feature of the silicone resins is discussed in detail; it is 230°C, and thus is by 100 °C higher than that of the most resistant purely organic high polymers. In combination with special pigments, it is even possible to produce films which are resistant to temperatures as high as 600 °C. The hydrophobic properties which are imparted to a surface even by very thin coatings of silicone resins, have been utilized particularly in the protection of buildings. By means of measured data it is possible to show that a silicone treatment prevents any penetration of water into porous materials up to pressures of 10 to 20 cm water gauge; this has however no influence whatsoever on the water and vapour permeability. An introductory section briefly explains the various liquid polysiloxane polymers which are already available as finished products and derives their property pattern from their constitution.